Re-examining the global urban hierarchy of corporate geography: the rise of Pacific Rim cities and shifting command-and-control - Vaněk, Patrik; Kouba, Luděk; Doyle, Eleanor (Bulletin of Geography. Socio-economic Series, 2025)
This paper investigates the dynamic evolution of world city hierarchy from 1996 to 2023, emphasising metropolitan areas as global command-and-control centres. It proposes a classification of the diverse literature on world/global cities and develops an analytical framework revisiting Godfrey and Zhou’s (1999) approach. Using data from the Fortune Global 500 list and Refinitiv Eikon database, the paper explores trends in global command-and-control centres by analysing the locations of corporate and regional headquarters. It confirms a shift towards Pacific Rim cities, driven by the emergence and rapid growth of firms from developing economies, particularly China. The findings highlight the strengthening role of US cities, the relative decline of Europe, and persistent global disparities in command-and-control. Beijing, in particular, rivals traditional centres such as New York, Tokyo and London, becoming a leading hub of global corporate power.